Ce-modified Pt / gamma-Al2O3 catalyst with low Pt load as well as preparation method and application of Ce-modified Pt / gamma-Al2O3 catalyst

Through Ce modified low-load Pt/γ-Al2O3 catalyst, the problem of high loading of precious metals and low-loading catalysts that have not been reported in the continuous process application of existing catalysts is solved, and the efficient catalytic hydrogenation of p-nitroanisole is achieved to prepare p-aminobenzole, which improves catalytic performance and stability.

CN119869518AActive Publication Date: 2025-04-25NANJING TECH UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510053996.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-25
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

When existing catalysts catalyze the hydrogenation of aromatic nitro compounds to prepare aromatic amino compounds, there is no relevant technical report on the continuous process application of low-loaded catalysts.

Method used

The low-load Pt/γ-Al2O3 catalyst modified with Ce modified Pt/γ-Al2O3 is promoted through a certain amount of Ce introduction to promote the dispersion of Pt particles and the interaction between the support and metal, thereby improving the reduction temperature and catalytic performance of the catalyst.

Benefits of technology

The catalytic performance and stability of the catalyst are improved, especially in continuous reactions, the conversion rate of p-nitroanisole and the yield of p-aminoanisole are significantly improved, and the cost is low.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869518A_ABST
    Figure CN119869518A_ABST
Patent Text Reader

Abstract

The invention provides a Ce-modified Pt / gamma-Al2O3 catalyst with low Pt load as well as a preparation method and application of the Ce-modified Pt / gamma-Al2O3 catalyst, and belongs to the field of catalysts. The method comprises the following steps: S1, adding deionized water into Al (OH) 3 powder, and then drying and extruding into strips to obtain strip-shaped Al (OH) 3; s2, carrying out first roasting on the strip-shaped Al (OH) 3 to obtain a gamma-Al2O3 carrier with a set particle size; s3, the gamma-Al2O3 carrier is soaked in a cerous nitrate aqueous solution, then drying and secondary roasting are conducted, and a Ce-modified gamma-Al2O3 catalyst is obtained; and S4, dipping the Ce modified gamma-Al2O3 catalyst in a chloroplatinic acid aqueous solution, and then carrying out drying and third roasting to obtain the Ce modified Pt / gamma-Al2O3 catalyst. Therefore, the catalytic performance of the fixed bed catalyst for the reaction of preparing p-anisidine through catalytic hydrogenation of p-nitroanisole is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of catalyst technology, and in particular to a Ce-modified low-Pt-loaded Pt / γ-Al2O3 catalyst and a preparation method and application thereof. Background Art

[0002] As an important basic raw material for fine chemicals, aromatic amino compounds are widely used in dyes, pigments, pesticides, medicines and fine chemicals, and have broad market prospects. There are many commonly used synthesis methods for aromatic amino compounds. In the early days, iron powder or alkali sulfide was used to reduce aromatic nitro compounds to prepare aromatic amino compounds. This method produces a large amount of wastewater and has great harm to the environment, and has been gradually eliminated. In recent years, the reduction method using hydrazine hydrate or sodium borohydride as a hydrogen source has shown good catalytic performance in the reduction of aromatic nitro compounds, but the cost of this method is too high and is not conducive to the large-scale production of aromatic amino compounds; the method of reducing aromatic nitro compounds by electrochemical reduction also shows excellent catalytic performance, but this method is more complicated and unstable, and the requirements for conditions are also more stringent, making it difficult to carry out large-scale production; and the catalytic hydrogenation method, as the most direct method for reducing aromatic nitro compounds, has the advantages of being environmentally friendly, good selectivity and high yield, and has become the ideal process for hydrogenating aromatic nitro compounds to prepare aromatic amino compounds in the current industry.

[0003] The hydrogenation of aromatic nitro compounds to prepare aromatic amino compounds is a typical reduction reaction, which often relies on catalysts. Researchers have studied a variety of catalysts for the catalytic hydrogenation of aromatic nitro compounds, including non-precious metal (Cu, Ni, etc.) and precious metal (Pt, Pd, Ru, etc.) catalysts. Although the cost of non-precious metal catalysts is lower than that of precious metal catalysts, their poor stability can easily lead to catalyst deactivation, and they are mostly used in intermittent reactors for the hydrogenation of aromatic nitro compounds, which has problems such as low efficiency; while precious metal catalysts are mostly used in the study of catalytic hydrogenation of nitrobenzene and its derivatives due to their excellent stability and high selectivity. Studies have shown that by modifying the carrier and then evenly dispersing 2.5% of Pd particles on the surface of the carrier, the catalyst can achieve high selectivity of p-nitroanisole to p-aminoanisole under mild conditions of 0.1Mpa H2 gas flow and 30°C reaction temperature. However, due to the influence of the -OCH3 substituent, it still faces the problem of low conversion rate of p-nitroanisole. Considering that the precious metal catalysts used in current research to catalyze the hydrogenation of aromatic nitro compounds have a high precious metal loading, the greatly increased cost limits their widespread use, and there are no related prior art reports on the continuous process for preparing p-aminoanisole by hydrogenation of p-nitroanisole using catalysts with low precious metal loadings. Summary of the invention

[0004] The present application provides a Ce-modified low-loaded Pt Pt / γ-Al2O3 catalyst and a preparation method and application thereof to solve the following technical problem: how to improve the catalytic performance of a fixed-bed catalyst for the reaction of catalytic hydrogenation of p-nitroanisole to prepare p-aminoanisole.

[0005] In a first aspect, the present application provides a method for preparing a Ce-modified low-loaded Pt Pt / γ-Al2O3 catalyst, the method comprising the following steps:

[0006] S1, adding deionized water to Al(OH)3 powder, and then drying and extruding into strips to obtain strip-shaped Al(OH)3;

[0007] S2, performing a first calcination on the strip-shaped Al(OH)3 to obtain a γ-Al2O3 carrier with a set particle size;

[0008] S3, immersing the γ-Al2O3 carrier in a cerium nitrate aqueous solution, followed by drying and a second calcination to obtain a Ce-modified γ-Al2O3 catalyst;

[0009] S4, immersing the Ce-modified γ-Al2O3 catalyst in an aqueous solution of chloroplatinic acid, followed by drying and a third calcination to obtain a Ce-modified Pt / γ-Al2O3 catalyst.

[0010] Optionally, the set particle size is 250-425 μm.

[0011] Optionally, the temperature of the first calcination is 800° C., and the time of the first calcination is 3 hours.

[0012] Optionally, the temperature of the second calcination is 800° C., and the time of the second calcination is 3 hours.

[0013] Optionally, the temperature of the third calcination is 450° C., and the time of the third calcination is 3 hours.

[0014] In a second aspect, the present application provides a Ce-modified Pt / γ-Al2O3 catalyst with low Pt loading prepared by the method described in any one of the embodiments in the first aspect.

[0015] Optionally, the mass fraction of Pt element in the Ce-modified γ-Al2O3 catalyst is 0.02%.

[0016] Optionally, the mass fraction of the Ce element in the Ce-modified γ-Al2O3 catalyst is 1 to 12%.

[0017] In the third aspect, the present application provides an application of a Ce-modified Pt / γ-Al2O3 catalyst with low Pt loading as described in any one of the embodiments in the second aspect, wherein the Ce-modified Pt / γ-Al2O3 catalyst with low Pt loading is used as a fixed bed catalyst for the reaction of catalytic hydrogenation of p-nitroanisole to prepare p-aminoanisole.

[0018] Optionally, after 18 hours of continuous reaction, the conversion rate of p-nitroanisole on the Ce-modified Pt / γ-Al2O3 catalyst is ≥85%, and the yield of p-aminoanisole is ≥85%.

[0019] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0020] The present application embodiment provides a method for preparing a Ce-modified low-load Pt Pt / γ-Al2O3 catalyst, which can promote the dispersion of Pt particles and strengthen the interaction between the carrier and the metal Pt by introducing a certain amount of Ce, thereby increasing the reduction temperature of the catalyst. At the same time, as the amount of Ce introduced increases, the oxygen vacancy concentration on the catalyst surface can be increased, the strong interaction between the metal-carrier is enhanced, and it is beneficial to promote the dispersion of the surface Pt particles, thereby increasing the adsorption amount of CO and the catalytic performance of the catalyst. Thereby improving the catalytic performance of the fixed bed catalyst for the reaction of catalytic hydrogenation of p-nitroanisole to prepare p-aminoanisole. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The accompanying drawings herein are incorporated in and constitute a part of the specification, illustrate embodiments consistent with the present application, and together with the description, are used to explain the principles of the present application.

[0022] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0023] Figure 1 A schematic flow chart of a method for preparing a Ce-modified low-Pt-loaded Pt / γ-Al2O3 catalyst provided in an embodiment of the present application;

[0024] Figure 2 XRD patterns of Pt / γ-Al2O3 catalysts modified with different mass fractions of Ce provided in this application;

[0025] Figure 3 Isothermal adsorption-desorption curves of Pt / γ-Al2O3 catalysts modified with different mass fractions of Ce provided in this application;

[0026] Figure 4 H2-TPR spectra of Pt / γ-Al2O3 modified with different mass fractions of Ce provided in this application;

[0027] Figure 5 X-ray photoelectron spectra of Ce 3d (a) and O1s (b) of Pt / γ-Al2O3 modified with different mass fractions of Ce provided in this application;

[0028] Figure 6 The conversion rate (a) of p-nitroanisole and the yield (b) of p-aminoanisole on the Pt / γ-Al2O3 catalyst modified with different mass fractions of Ce provided in this application. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0030] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0031] Example 1

[0032] Figure 1 A schematic flow chart of a method for preparing a Ce-modified low-Pt-loaded Pt / γ-Al2O3 catalyst provided in an embodiment of the present application.

[0033] like Figure 1 As shown, this embodiment provides a method for preparing a Ce-modified low-loaded Pt Pt / γ-Al2O3 catalyst, the method comprising the following steps:

[0034] Step 1, weigh a certain amount of Al(OH)3 powder (chemically pure, Sinopharm Chemical Reagent Co., Ltd.), add deionized water, stir thoroughly until the mixture is evenly mixed, put it in a 110°C oven to dry for a certain period of time, take it out and extrude it into strips, put it in the oven again for 3 hours, take it out and put it in a muffle furnace to roast it at 800°C for 3 hours, take it out and grind and sieve it to obtain a γ-Al2O3 carrier with a particle size of 250-425μm;

[0035] Step 2, weigh a certain amount of γ-Al2O3 carrier and immerse it in an aqueous solution of cerium nitrate (analytical grade, Shanghai McLean Biochemical Technology Co., Ltd.), let it stand at room temperature for 18 hours, and then place it in a 110°C oven. After being completely dried, put it in a muffle furnace and roast it at 800°C for 3 hours, and then immerse it in an aqueous solution of chloroplatinic acid (analytical grade, Sinopharm Chemical Reagent Co., Ltd.) and immerse it in an equal volume. After standing and drying, place it in a muffle furnace and roast it at 450°C for 3 hours to obtain a Ce-modified Pt / γ-Al2O3 catalyst. The mass fraction of Pt element in the catalyst is 0.02%, and the mass fraction of Ce element is 1%. The Ce-modified Pt / γ-Al2O3 catalyst of Example 1 is named Pt / 1Ce / γ-Al2O3 catalyst.

[0036] Example 2

[0037] This embodiment is modified as follows based on the disclosure of Embodiment 1:

[0038] The mass fraction of Pt element in Ce-modified Pt / γ-Al2O3 catalyst is 0.02%, and the mass fraction of Ce element is 3%.

[0039] The Ce-modified Pt / γ-Al2O3 catalyst of Example 2 is named Pt / 3Ce / γ-Al2O3 catalyst.

[0040] Example 3

[0041] This embodiment is modified as follows based on the disclosure of Embodiment 1:

[0042] The mass fraction of Pt element in Ce-modified Pt / γ-Al2O3 catalyst is 0.02%, and the mass fraction of Ce element is 6%.

[0043] The Ce-modified Pt / γ-Al2O3 catalyst of Example 3 is named Pt / 6Ce / γ-Al2O3 catalyst.

[0044] Example 4

[0045] This embodiment is modified as follows based on the disclosure of Embodiment 1:

[0046] The mass fraction of Pt element in Ce-modified Pt / γ-Al2O3 catalyst is 0.02%, and the mass fraction of Ce element is 12%.

[0047] The Ce-modified Pt / γ-Al2O3 catalyst of Example 4 is named as Pt / 12Ce / γ-Al2O3 catalyst.

[0048] Comparative Example 1

[0049] This comparative example provides a Pt / γ-Al2O3 catalyst prepared in step 1 of Example 1.

[0050] The catalysts obtained in Examples 1 to 4 and Comparative Example 1 were characterized, and the specific characterization method is as follows:

[0051] The X-ray diffraction analysis (XRD) of the catalyst samples was performed on a Smart Lab X-ray diffractometer (Rigaku, Japan). First, the calcined catalyst samples were reduced on the adsorption instrument at a reduction temperature of 300 °C and a high-purity H2 gas flow of 30 mL / min for 2 h. Then, the samples were ground into powder and placed on the X-ray diffractometer with a scanning angle of 10 to 80° and a flow rate of 20° min. -1 The instrument uses a Cu target Kα line source, a tube current of 100mA and a tube voltage of 40kV.

[0052] The specific surface area, pore volume and pore size analysis (BET) of the catalyst samples were measured on a Belsorp-Ⅱ adsorption instrument (BEL, Japan). First, the calcined catalyst samples were reduced on the adsorption instrument at a reduction temperature of 300°C and a high-purity H2 gas flow of 30 mL / min for 2 hours, and then about 0.2 g of the sample was weighed for vacuum pretreatment at a treatment temperature of 300°C and a time of 6 hours. After the treatment, N2 adsorption-desorption test was performed in liquid nitrogen at -196°C. The specific surface area was calculated using the BET equation, and the pore size and pore volume were calculated using the BJH equation.

[0053] The CO pulse adsorption analysis of the catalyst samples was performed on a TP-5000-Ⅱ multi-purpose adsorption instrument (Tianjin Xianquan Company). The main steps are as follows: first, 0.5 g of sample was placed in the middle of the quartz tube of the instrument, then the temperature was raised to 300 °C and maintained for 2.5 h, during which time 30 mL min -1 The high-purity H2 gas flow was continuously purged for 2 h, and then switched to 30 mL min -1 The He gas flow was purged again for 0.5 h, then cooled to 30 °C and maintained, and finally 10 pulse injections of 100 μL of CO-He mixed gas (CO (10%)-He (90%)) were performed. The flow change of the tail gas after dehydration was detected by a thermal conductivity detector (TCD) and the pulse adsorption diagram was recorded.

[18] The CO adsorption per unit mass of catalyst was calculated based on the peak area.

[0054] The H2-TPR analysis of the catalyst samples was carried out on a TP-5000-Ⅱ multi-purpose adsorption instrument (Tianjin Xianquan Company). The main steps were as follows: first, 0.2 g of sample was placed in the middle of the quartz tube of the instrument, then the temperature was raised to 200 °C and maintained for 1 h, during which time 30 mL min -1 The high-purity N2 gas flow was continuously purged, and after the purging was completed, it was cooled to 30℃ and maintained, and finally switched to 30mL·min -1 H2-N2 mixed gas (H2(10%)-N2(90%)) at 10℃·min -1 The temperature was raised to 600°C at a rate, and a thermal conductivity detector (TCD) was used to detect the change in the tail gas flow rate after dehydration and record the reduction curve, which was calibrated by injecting a known amount of H2.

[0055] The X-ray electron spectroscopy (XPS) of the catalyst samples was characterized on a Kratoms axis supratm instrument (Shimadzu Corporation, Japan). The calcined catalyst samples were first reduced on the adsorption instrument, reduced at a reduction temperature of 300°C and a high-purity H2 gas flow of 30 mL / min for 2 h, and then X-ray electron spectroscopy was performed. The incident radiation was monochromatic AlKα (1486.6 eV, 15 kV), and the charge correction standard was C1s (284.8 eV).

[0056] The characterization results of the catalysts obtained in Examples 1 to 4 and Comparative Example 1 are as follows:

[0057] Figure 2 XRD patterns of Pt / γ-Al2O3 catalysts modified with different mass fractions of Ce provided in this application;

[0058] In order to explore the effect of the introduction of different mass fractions of Ce on the phase structure of Pt / γ-Al2O3 catalyst, XRD analysis was performed on the catalyst samples. The results are as follows: Figure 2 As shown. Figure 2It can be seen that the catalysts of Pt / γ-Al2O3 and Pt / 1Ce / γ-Al2O3 all have the same characteristic diffraction peaks belonging to γ-Al2O3 (PDF#10-0425) at 2θ=37.6°, 39.4°, 45.8°, and 67.0°. The catalyst of Pt / 1Ce / γ-Al2O3 does not have the characteristic diffraction peak of Ce, which indicates that Ce is well dispersed on the support surface and has no effect on the crystal structure of γ-Al2O3. The catalysts of Pt / 3Ce / γ-Al2O3, Pt / 6Ce / γ-Al2O3, and Pt / 12Ce / γ-Al2O3 have the same characteristic diffraction peaks at 2θ=37.6°, 39.4°, 45.8°, and 67.0°. The catalysts all showed characteristic diffraction peaks belonging to γ-Al2O3 at 2θ=37.6°, 39.4°, 45.8°, and 67.0°, and characteristic diffraction peaks belonging to CeO2 (PDF#34-0394) at 2θ=28.5°, 33.0°, and 56.3°. The intensity of the characteristic diffraction peak of γ-Al2O3 of the catalyst samples at 2θ of 45.8° and 67.0° gradually decreased, and the intensity of the characteristic diffraction peak of CeO2 of the catalyst samples at 2θ of 28.5°, 33.0°, 47.4°, 56.3°, 76.6°, and 79.0° gradually increased. The results show that the introduction of Ce has no obvious effect on the crystal phase of the γ-Al2O3 carrier, but with the increase of the introduced Ce, the agglomeration of CeO2 fluorite structure will gradually form on the surface of the γ-Al2O3 carrier and exceed the monolayer coverage of γ-Al2O3 on the carrier surface, resulting in the decrease of the intensity of some γ-Al2O3 characteristic diffraction peaks and the enhancement of the intensity of CeO2 characteristic diffraction peaks.

[0059] The results of specific surface area, pore volume and average pore size of Pt / γ-Al2O3 catalysts modified with different mass fractions of Ce are shown in Table 1.

[0060] Table 1 Textural properties of Pt / γ-Al2O3 catalysts modified with different mass fractions of Ce

[0061]

[0062] As shown in Table 1, with the increase of Ce mass fraction, the specific surface area of ​​the catalyst sample decreased from 197 to 154 m 2 ·g -1 , the pore volume decreased from 0.58 to 0.48 cm 3 ·g -1, the average pore size remains unchanged, all at 13.91nm. The results show that the introduction of Ce has a great influence on the specific surface area. Combined with XRD, it can be inferred that as the amount of Ce introduced increases, the CeO2 fluorite structure formed on the surface of the γ-Al2O3 carrier gradually increases, causing the carrier surface to shrink, resulting in a decrease in specific surface area, and a small amount of CeO2 enters the interior of the carrier to reduce the pore volume; while the average pore size remains unchanged, indicating that the introduction of Ce does not block the pores. In general, it is believed that catalysts with higher specific surface areas exhibit better catalytic performance. Although the specific surface area of ​​the Pt / γ-Al2O3 catalyst is the highest among all samples, the Pt / 6Ce / γ-Al2O3 catalyst with a lower specific surface area exhibits the best catalytic performance. This result shows that the specific surface area is not the key factor in determining catalytic performance.

[0063] Figure 3 The isothermal adsorption-desorption curves of the Pt / γ-Al2O3 catalyst modified with different mass fractions of Ce provided in this application.

[0064] Figure 3 Nitrogen adsorption-desorption isotherms for all catalysts are shown. Figure 3 It can be seen that all catalysts have Langmuir IV type adsorption-desorption isotherms, and the adsorption hysteresis loop is an H1 type hysteresis loop, indicating that all catalysts are mesoporous materials with open ends and uniform diameter distribution, and the introduction of Ce does not affect the mesoporous structure of the catalyst.

[0065] The uniform dispersion of precious metal Pt on the carrier is a key factor affecting the activity of supported Pt-based catalysts. The agglomeration of Pt particles on the carrier surface will lead to a decrease in catalyst activity and catalyst deactivation. Therefore, by performing CO pulse adsorption on Pt / γ-Al2O3 catalysts modified with different mass fractions of Ce, the CO adsorption amount of Pt on the catalyst was calculated, and the irreversible chemical adsorption amount of CO on Pt-based catalysts was used to study the dispersion differences of Pt particles on the carrier surface. The results are shown in Table 2 below. As shown in Table 2, the CO adsorption amount of unreduced Pt / γ-Al2O3 and Pt / nCe / γ-Al2O3 catalysts is 0, and the reduced catalysts all have CO adsorption, indicating that only the zero-valent Pt particles on the catalyst surface adsorb CO. Compared with the Pt / γ-Al2O3 catalyst, the CO adsorption amount of the Pt / nCe / γ-Al2O3 catalyst has increased, and the Ce content shows a gradual increase from 0% to 6%: from 2.0μmol·g -1 Gradually increased to 4.2 μmol·g -1 This may be due to the fact that the introduction of Ce increased the oxygen vacancy concentration on the support surface, promoted the dispersion of Pt particles, and enhanced the strong interaction between metal and support. The CO adsorption capacity caused by the introduction of 12Ce decreased to 2.8 μmol·g-1 This may be due to the excessive Ce introduction, which covered the active centers on the catalyst surface, resulting in uneven dispersion of Pt particles and partial agglomeration of Pt particles, which greatly reduced the CO adsorption. In summary, the introduction of Ce can promote the dispersion of Pt on the support surface, but the introduction of too much Ce is not conducive to the dispersion of Pt.

[0066] Table 2 CO adsorption amount of Pt on the surface of Pt / γ-Al2O3 catalysts modified with different mass fractions of Ce

[0067] catalyst Reduction conditions <![CDATA[CO adsorption amount (μmol·g -1 )]]> <![CDATA[Pt / γ-Al2O3]]> Unrestored 0.0 <![CDATA[Pt / nCe / γ-Al2O3]]> Unrestored 0.0 <![CDATA[Pt / γ-Al2O3]]> <![CDATA[Reduce with flowing H2 at 300°C for 2 h]]> 2.0 <![CDATA[Pt / 1Ce / γ-Al2O3]]> <![CDATA[Reduce with flowing H2 at 300°C for 2 h]]> 2.9 <![CDATA[Pt / 3Ce / γ-Al2O3]]> <![CDATA[Reduce at 300 °C for 2 h with H2 flowing down]]> 3.6 <![CDATA[Pt / 6Ce / γ-Al2O3]]> <![CDATA[Reduce at 300 °C for 2 h with H2 flowing down]]> 4.2 <![CDATA[Pt / 12Ce / γ-Al2O3]]> <![CDATA[Reduce at 300 °C for 2 h with H2 flowing down]]> 2.8

[0068] Figure 4 The H2-TPR spectra of Pt / γ-Al2O3 modified with different mass fractions of Ce provided in this application.

[0069] In order to investigate the effect of the introduction of Ce on the reduction performance of Pt / γ-Al2O3 catalyst, H2-TPR detection was performed on catalyst samples modified with different mass fractions of Ce. The results are shown in Figure 4 As shown. Figure 4 It can be seen that in the temperature range of 100-600℃, the catalyst samples all show an obvious reduction peak, which is the PtO x (x represents the number of oxygen elements). The reduction peak of the Pt / γ-Al2O3 catalyst is 269°C. When the Ce mass fraction increases to 6%, the reduction peak temperature of the catalyst gradually increases to 395°C; and when the Ce introduction amount is 12%, the reduction temperature of the catalyst slightly decreases to 385°C.

[0070] Table 3 H2 consumption of Pt / γ-Al2O3 catalysts modified with different mass fractions of Ce

[0071] sample <![CDATA[H2 consumption / (μmol·g -1 )]]> <![CDATA[Pt / γ-Al2O3]]> 30.3 <![CDATA[Pt / 1Ce / γ-Al2O3]]> 64.9 <![CDATA[Pt / 3Ce / γ-Al2O3]]> 91.1 <![CDATA[Pt / 6Ce / γ-Al2O3]]> 93.6 <![CDATA[Pt / 12Ce / γ-Al2O3]]> 126.5

[0072] It can be seen from Table 3 that the H2 consumption of Pt / γ-Al2O3 catalyst is only 30.3 μmol·g -1 With the increase of Ce mass fraction, the H2 consumption of the catalyst showed a gradual increase trend: from 30.3 μmol·g -1 Gradually increased to a maximum value of 126.5 μmol·g -1 In summary, with the introduction of a certain amount of Ce, the interaction between the metal and the support in the catalyst is enhanced, which promotes the dispersion and stability of Pt on the surface, resulting in a significant increase in the strength of the Pt-O bond. xThe reduction activation energy increases, so the reduction peak temperature of the catalyst gradually increases and the H2 consumption gradually increases, but this may also be affected by hydrogen overflow leading to the reduction of a very small part of CeO2 on the surface; but the introduction of too much Ce will lead to a decrease in the active centers on the carrier surface, making the Pt particles unevenly dispersed and causing agglomeration, thereby slightly lowering the reduction temperature of the catalyst.

[0073] Figure 5 X-ray photoelectron spectra of Ce 3d (a) and O1s (b) of Pt / γ-Al2O3 modified with different mass fractions of Ce provided in this application.

[0074] The surface electronic states and atomic concentrations of Ce and O in the reduced Pt / γ-Al2O3 catalysts modified with different mass fractions of Ce were studied by XPS analysis. Figure 5 The Ce 3d (a) and O1s (b) spectra of the Pt / nCe / γ-Al2O3 catalyst are depicted. Figure 5 (a) It can be seen that the two main regions of the Ce 3d spectrum, 880-897 and 898-917 eV, are related to the Ce 3d 5 / 2 (v) and Ce3d 3 / 2 (u) is consistent. The 3d peak of Ce is decomposed into 10 peaks, and the v1, v3, u2 and u4 peaks are attributed to Ce. 3+ , Ce 4+ Including v2, v4, u1, u3, u5 and u6 peaks. The O1s spectrum of the reduced catalyst is as follows Figure 5 As shown in (b), all catalysts show three clear peaks in the O1s spectrum, located at around 530, 530.9 and 531.8 eV, respectively. The first peak is located at 530 eV, which is attributed to the lattice oxygen (O L =O 2- ); the second peak is located at 530.9±0.1eV, which is attributed to surface oxygen defects or weakly adsorbed oxygen ions (O D =O2 2- Or - ); the third peak is located at 531.8±0.17 eV, which is attributed to the surface hydroxyl group (O H ) The valence states and relative contents of Ce and O on the reduced Pt / nCe / γ-Al2O3 catalyst are summarized in Table 4, and the relative contents were calculated by peak fitting and using the area under the fitted components.

[0075] Table 4 Surface atomic valence states and relative contents of Ce-modified Pt / γ-Al2O3 catalysts with different mass fractions

[0076]

[0077] As shown in Table 4, as the mass fraction of Ce increases from 1% to 12%, the Ce content in the catalyst increases. 3+ The relative content of CeO2 increases linearly from 15.6% to 33.5%, reaching the maximum value of the sample. In addition, the migration of oxygen in ceria is mainly carried out through vacancy hopping, so CeO2 is also commonly used. 3+ and (Ce 3+ +Ce 4+ ) ratio to evaluate the formation of oxygen vacancies, so Ce 3+ and (Ce 3+ +Ce 4+ ) has a certain linear relationship with the oxygen vacancy concentration on the catalyst surface, which is also consistent with the O D / (O L +O D +O H ) ratio increases with Ce 3+ and (Ce 3+ +Ce 4+ ) increases. This trend is also consistent with the catalytic performance of the catalyst. With the increase of the mass fraction of Ce, the oxygen vacancy concentration increases linearly, and the initial conversion rate of p-nitroanisole and the initial yield of p-aminoanisole gradually increase to 100% and 99%, respectively. However, the introduction of too much Ce is not good for the stability of the catalyst, which shows that the introduction of Ce is closely related to the catalytic performance.

[0078] Example 5

[0079] This embodiment provides an application of a Ce-modified Pt / γ-Al2O3 catalyst with low Pt loading, wherein the Ce-modified Pt / γ-Al2O3 catalyst with low Pt loading is used as a fixed bed catalyst for the reaction of catalytic hydrogenation of p-nitroanisole to prepare p-aminoanisole. The specific application process is as follows:

[0080] The reaction of catalytic hydrogenation of p-nitroanisole to prepare p-aminoanisole was carried out in a continuous flow fixed bed reactor (500mm×10mm), with a catalyst loading of 0.2g (particle size of 250-425μm), mixed with quartz sand to reduce the reaction heat and disperse evenly in the middle section of the tube, and pure quartz sand was filled in the upper and lower sections. Before the reaction, a high-purity H2 flow (50mL·min) at 300℃ and 0.5Mpa was used. -1 ) for 4 h, then cooled to 55 °C and pressurized to 1 MPa of high-purity H2 (50 mL min -1 ), a 10% mixed solution of p-nitroanisole (chemically pure, Sinopharm Chemical Reagent Co., Ltd.) and ethanol (chemically pure, Sinopharm Chemical Reagent Co., Ltd.) was pumped into the tube by a double-plunger micropump. The mass space velocity of p-nitroanisole was 1.25 h -1The p-nitroanisole mixed solution was mixed with high-purity H2 gas flow at the top of the reaction tube and then entered the catalyst bed. The reaction temperature was controlled by a temperature controller to maintain at about 60°C. After the products were separated by a gas-liquid separator, the liquid products were quantitatively analyzed using the peak area normalization method on a GC-3900 gas chromatograph (Tengzhou Ruineng Analytical Instrument Co., Ltd.).

[0081] Figure 6 The conversion rate (a) of p-nitroanisole and the yield (b) of p-aminoanisole on the Pt / γ-Al2O3 catalyst modified with different mass fractions of Ce provided in this application.

[0082] Depend on Figure 6 (a) and (b) show that: after 18 hours of continuous reaction, the conversion rate of p-nitroanisole on the Pt / γ-Al2O3 catalyst is 71%, and the yield of p-aminoanisole is 67%; the conversion rate of p-nitroanisole on the Pt / 1Ce / γ-Al2O3 catalyst is 89%, and the yield of p-aminoanisole is 88%; the conversion rate of p-nitroanisole on the Pt / 3Ce / γ-Al2O3, Pt / 6Ce / γ-Al2O3 and Pt / 12Ce / γ-Al2O3 catalysts is 100%, and the yield of p-aminoanisole is 99%. After 54 hours of continuous reaction, the conversion rate of p-nitroanisole on the Pt / γ-Al2O3 catalyst was 58% and the yield was 56%; the conversion rate of p-nitroanisole on the Pt / 1Ce / γ-Al2O3 catalyst was 66% and the yield of p-aminoanisole was 65%; the conversion rate of p-nitroanisole on the Pt / 3Ce / γ-Al2O3 catalyst was 75% and the yield of p-aminoanisole was 74%; the conversion rate of p-nitroanisole on the Pt / 6Ce / γ-Al2O3 catalyst was 100% and the yield of p-aminoanisole was 99%; the conversion rate of p-nitroanisole on the Pt / 12Ce / γ-Al2O3 catalyst was 89% and the yield of p-aminoanisole was 87%. The experimental results show that compared with the Pt / γ-Al2O3 catalyst, the conversion rate and yield of the Pt / γ-Al2O3 catalyst introduced with Ce are greatly improved, indicating that the introduction of Ce promotes the catalytic performance and stability of the Pt / γ-Al2O3 catalyst; when the Ce mass fraction is 12%, after 54 hours of reaction, the catalytic performance and stability of the catalyst show a slight downward trend, indicating that excessive introduction of Ce is not conducive to the catalytic performance and stability of the catalyst; when the Ce mass fraction is 6%, the catalytic performance and stability of the catalyst are the best, and the activity of the catalyst remains unchanged within 54 hours of continuous reaction, the conversion rate of p-nitroanisole remains at 100%, and the yield of p-aminoanisole is stably maintained at more than 99%. However, the stability of the catalyst in the long-term catalytic hydrogenation of p-nitroanisole to prepare p-aminoanisole remains to be explored, which was not carried out due to limited experimental conditions and time.

[0083] In addition, one or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:

[0084] In the embodiment of the present invention, as the amount of Ce introduced increases, CeO2 agglomerates will form on the catalyst surface, affecting the crystal structure of the catalyst and reducing the specific surface area of ​​the catalyst. A small amount of CeO2 will enter the interior of the catalyst, resulting in a slight decrease in the pore volume.

[0085] In the embodiment of the present invention, the introduction of a certain amount of Ce can promote the dispersion of Pt particles and strengthen the interaction between the carrier and metal Pt, thereby increasing the reduction temperature of the catalyst; however, excessive introduction can easily lead to the covering of the active centers on the surface of the γ-Al2O3 carrier, causing some Pt ​​particles to be unevenly dispersed and agglomerate, thereby causing a slight decrease in the reduction temperature of the catalyst.

[0086] In the embodiment of the present invention, as the amount of Ce introduced increases, the oxygen vacancy concentration on the catalyst surface can be increased, the strong interaction between the metal and the support is enhanced, which is beneficial to promote the dispersion of surface Pt particles, thereby increasing the adsorption amount of CO and the catalytic performance of the catalyst, but it is not a decisive factor in the catalytic performance of the catalyst.

[0087] In the embodiment of the present invention, compared with the Pt / γ-Al2O3 catalyst, the introduction of Ce can greatly improve the catalytic performance and stability of the catalyst. When the mass fraction of Ce is 6%, the conversion rate of p-nitroanisole and the yield of p-aminoanisole shown by the catalyst are the best, and there is no obvious decline after 54 hours of continuous reaction.

[0088] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0089] In addition, in the description of the present application, the terms "include", "comprise", etc. mean "including but not limited to". In this document, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations.

[0090] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A method for preparing a Ce-modified low-loaded Pt Pt / γ-Al2O3 catalyst, characterized in that: The method comprises the following steps: S1, adding deionized water to Al(OH)3 powder, and then drying and extruding into strips to obtain strip-shaped Al(OH)3; S2, performing a first calcination on the strip-shaped Al(OH)3 to obtain a γ-Al2O3 carrier with a set particle size; S3, immersing the γ-Al2O3 carrier in a cerium nitrate aqueous solution, followed by drying and a second calcination to obtain a Ce-modified γ-Al2O3 catalyst; S4, immersing the Ce-modified γ-Al2O3 catalyst in an aqueous solution of chloroplatinic acid, followed by drying and a third calcination to obtain a Ce-modified Pt / γ-Al2O3 catalyst.

2. The method for preparing the Ce-modified low-loaded Pt Pt / γ-Al2O3 catalyst according to claim 1, characterized in that: The set particle size is 250-425 μm.

3. The method for preparing the Ce-modified low-loaded Pt Pt / γ-Al2O3 catalyst according to claim 1, characterized in that: The temperature of the first calcination is 800° C., and the time of the first calcination is 3 hours.

4. The method for preparing the Ce-modified low-loaded Pt Pt / γ-Al2O3 catalyst according to claim 1, characterized in that: The temperature of the second calcination is 800° C., and the time of the second calcination is 3 hours.

5. The method for preparing the Ce-modified low-loaded Pt Pt / γ-Al2O3 catalyst according to claim 1, characterized in that: The temperature of the third calcination is 450° C., and the time of the third calcination is 3 hours.

6. A Ce-modified Pt / γ-Al2O3 catalyst with low Pt loading prepared by the method according to any one of claims 1 to 5.

7. The Ce-modified low-Pt-loaded Pt / γ-Al2O3 catalyst according to claim 6, characterized in that: The mass fraction of Pt element in the Ce-modified γ-Al2O3 catalyst is 0.02%.

8. The Ce-modified low-Pt-loaded Pt / γ-Al2O3 catalyst according to claim 6, characterized in that: The mass fraction of Ce element in the Ce-modified γ-Al2O3 catalyst is 1% to 12%.

9. Use of a Ce-modified low-Pt-loaded Pt / γ-Al2O3 catalyst according to any one of claims 6 to 8, characterized in that: The Ce-modified Pt / γ-Al2O3 catalyst with low Pt loading is used as a fixed bed catalyst for the reaction of preparing p-aminoanisole by catalytic hydrogenation of p-nitroanisole. The use of the Ce-modified low-Pt-loaded Pt / γ-Al2O3 catalyst according to claim 9, characterized in that: After 18 hours of continuous reaction, the conversion rate of p-nitroanisole on the Ce-modified Pt / γ-Al2O3 catalyst was ≥85%, and the yield of p-aminoanisole was ≥85%.

Citation Information

Patent Citations

  • Method for producing anisidine by mixed nitrochlorobenzene reacting in aqueous solvent

    CN101607919A

  • Supported noble-metal hydrogenation catalyst, and preparation method and application of catalyst

    CN107469813A

  • Pt-based dehydrogenation catalyst and preparation method thereof

    CN108786801A

  • Supported Catalyst Used For Synthesizing Polyether Amine, And Manufacturing Method

    US20190201878A1

  • Process for the preparation of aromatic dialkylamines

    US4760183A